2019
DOI: 10.1556/2006.8.2019.45
|View full text |Cite
|
Sign up to set email alerts
|

Reducing compulsive Internet use and anxiety symptoms via two brief interventions: A comparison between mindfulness and gradual muscle relaxation

Abstract: Background Compulsive Internet use (CIU) refers to those individuals who experience a loss of control regarding their online use. Although suffered by a minority, a much larger proportion of adults report to be experiencing early signs of CIU, which can become more problematic if sustained over time, especially when used as a coping mechanism for stress. Since compulsive behaviors are characterized by executing behaviors on “automatic pilot,” mindfulness techniques, which help individuals relate more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(25 citation statements)
references
References 43 publications
(54 reference statements)
0
24
0
1
Order By: Relevance
“…Before computing the results, we excluded two effect sizes from two different studies (Khazaei et al, 2017; Quinones and Griffiths, 2019) from entering the meta-analysis for PIU, since their magnitude of effect differs substantially from the remaining studies ( g = −5.75 for the mindfulness intervention in Quinones and Griffiths, 2019, and g = −4.88 for a range of positive psychology interventions in Khazaei et al, 2017, see further details in Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Before computing the results, we excluded two effect sizes from two different studies (Khazaei et al, 2017; Quinones and Griffiths, 2019) from entering the meta-analysis for PIU, since their magnitude of effect differs substantially from the remaining studies ( g = −5.75 for the mindfulness intervention in Quinones and Griffiths, 2019, and g = −4.88 for a range of positive psychology interventions in Khazaei et al, 2017, see further details in Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Instruments varied between the studies. However, for PIU most common symptoms assessed were compulsive Internet use, negative outcomes, mood alterations (withdrawal) and tolerance (Cardak et al, 2009; Khazaei et al, 2017; Kim, 2008; Liu et al, 2015; Pan, 2020; Quinones and Griffiths, 2019; Su et al, 2011; Yang and Kim, 2018). Where reported, reliability of measurements was high and Cronbach’s alpha values of the instruments above 0.80 (Hou et al, 2019; Kim, 2008; Liu et al, 2015; Pan, 2020; Quinones and Griffiths, 2019; Yang and Kim, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Focusing on self-motion combined with repeated rotations through “contract–relaxation–recontract” cycles of muscle movements, it may be that athletes have a sophisticated understanding of voluntary relaxation of their whole-body muscle, better cognize intense reflection, and thus control the intensity of the whole-body muscle, leading to peace and decreased negative emotions such as anxiety, depression, and fear ( Zhao et al, 2016 ). Therefore, through peace and relaxation of the whole-body muscle, PRT inhibits anxiety induced by particular environments, such as general anxiety reactions ( Dolbier and Rush, 2012 ; Allison et al, 2019 ; Quinones and Griffiths, 2019 ), specialized speech phobia ( Hazlett-Stevens and Borkovec, 2001 ), and preexamination anxiety ( Wachelka and Katz, 1999 ; Dehghan-Nayeri and Adib-Hajbaghery, 2011 ; O’Donnell and Dunlap, 2019 ; Gallego-Gómez et al, 2020 ), as reported in recent research. Among these studies, the most commonly reported effects pertained to the release of anxiety among collegiate students ( Wachelka and Katz, 1999 ; Dehghan-Nayeri and Adib-Hajbaghery, 2011 ; Dolbier and Rush, 2012 ; Allison et al, 2019 ).…”
Section: Introductionmentioning
confidence: 68%
“…The objective of this approach is to help individuals change the way they think through mindfulness meditation and exercises. The abbreviated 2-week MBSR mainly includes Body Scan Mediation and Sitting Mediation used audio recordings from an online version of the Kabat-Zinn course (made by a certified MBSR instructor) and previous studies (Quinones and Griffiths, 2019 ; Wathugala et al, 2019 ; Potter, 2020 ). On the first day (the start of week 1), the participant will be taught what MBSR and Body Scan Mediation are by an expert, and all participants will practice daily while being individually guided by the special audio during days 2–14.…”
Section: Methodsmentioning
confidence: 99%
“…At present, mindfulness-based stress reduction (MBSR) and psychological consultation guided by the needs assessment tool (NST) are relatively widely used among FCs of advanced cancer patients (Zhang et al, 2015;Zimmermann et al, 2018). Previous studies found that both classic 8-week MBSR sessions and abbreviated 2-week sessions were effective in reducing depression, anxiety, and distress (Grossman et al, 2004;Khoury et al, 2015;Quinones and Griffiths, 2019;Wathugala et al, 2019). MBSR helps FCs focus on the current physical and mental state, primarily through meditation, to accept the state in a positive way.…”
Section: Introductionmentioning
confidence: 99%